THE INFLUENCE OF GREEN HOTEL AND SERVICE QUALITY ON COSTUMER SATISFACTION IN MADANI HOTEL MEDAN - Ika Melati Puji Asputri; Adelina Lubis; Sugito Sugito (Jurnal Ekonomi, 2023)
This study aims to determine the effect of Green Hotel and Service Quality on Madani Hotel Medan guest satisfaction. The sample in this study was 98 guests. Multiple linear regression and hypothesis testing are the analytical methods used. The results showed that Green Hotel significantly affected guest satisfaction at Madani Hotel Medan. Service quality affects guest satisfaction at Madani Hotel Medan. Many consumers or guests who want a friendly hotel environment. Therefore, green hotels can form the basis for a marketing strategy great. The quality of service at the hotel is good, and guest satisfaction is high. After the guest is satisfied with the product or service received, guests compare the services provided. If the guest is delighted, they encourage others to buy from the exact location again. Therefore, hotels need to start thinking more maturely about the importance of customer service through service quality. Meanwhile, customer service and satisfaction are increasingly being recognized as important aspects of survival and competitiveness in business.